Incidencia de las dificultades de aprendizaje en el proceso de enseñanza de la lecto-escritura de los estudiantes de primer año de educación básica del jardín de infantes Cruz García Cajamarca, de la ciudad de Santa Rosa, periodo lectivo 2010-2011. - Azuero Pereira, Ruth del Cisne (2011)
Learning disabilities are a generic term that refers to a heterogeneous group of disorders manifested by significant difficulties in the acquisition and use of the ability to understand, speak, read, write, reasoning or mathematics. For children with learning difficulties work it is meaningless because it gives no fruit, so we have to take action as soon as possible to treat children with learning disabilities.